ANALISIS E – SERVICE QUALITY PADA APLIKASI STUDENT ADMISSION SMB TELKOM UNIVERSITY - Sijabat, Astriyani; Widaningsih , Sri; Mustikasari, Ati (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
Telkom University is the best private university with the No.1 ranking in Indonesia which has changed the entire process of accepting prospective students using technology that is currently developing. The number of registrants that continues to increase in each year of admission makes Telkom University innovate to simplify the registration process for prospective students by creating a website-based application called "Student Admission" which is connected from the SMB Telkom website. The purpose of this study is to measure the dimensions of E - Service Quality contained in the Student Admission application on the quality and satisfaction of prospective new students at Telkom University. The method used in this research is descriptive quantitative method with the data used are primary data and secondary data, data collection techniques using interviews, observations, and questionnaires. Data collection using a population of prospective new students with a sample of 100 respondents. In this research, the dataanalysis technique used is descriptive analysis with the Importance Performance Analysis (IPA) and CustomerSatisfaction Index (CSI) methods. The results of the calculation of descriptive analysis show that reality and expectations get a score of 84.14 (very good) and 87.76 (very important). In the CSI calculation results, the result is 80.50 which indicates that prospective new students are satisfied with the Student Admission application service. The Importance Performance Analysis method shows that in quadrant A (top priority) regarding website access, information, features, PIN validation, theservices provided need to be improved.